ChemInform Abstract: A Catalytic Asymmetric Ugi‐Type Reaction with Acyclic Azomethine Imines. Issue 1 (3rd January 2013) - Hashimoto, Takuya; Kimura, Hidenori; Kawamata, Yu; Maruoka, Keiji
Abstract In the presence of axially chiral dicarboxylic acid BNDA as catalyst, 2‐benzoyloxyaryl isocyanides react with azomethine imines generated in situ from aldehydes and benzhydrazide (II), to give oxadiazine derivatives (IV).